“Artist’s book” as intermedia discourse - Bobilewicz, Grażyna (Wydawnictwo Naukowe UAM, 2012)
The article is devoted to an analysis of various representations of the “Artist’s book” genre in modern Russian and world art. These representations function within the framework of the paradigm of art that refers to issues such as inter- and multimedia, the model of a broadly talented artist, the concept of a multi-material work of art and the interactive act of perception. The analysis of the issues connected with verbal and visual representations of the “Artist’s book” has been based on the superordinate ‘word and picture’ formula and the interpretative indicators determined by generic diversification and the dialogue with other kinds of art: the relationship with painting and sculpture, the book as an object, ready made, mail-art, an artistic project (audiovisual book, photo- and body-art book, book-performance), as well as by the act of reception. In intermedia discourse, the “Artist’s book” functions within the cultural, artistic and aesthetic perspective, between art and communication.
Keywords: “Artist’s book”; Intermedia; Multimedia; Modern Russian art; Word; Picture